Germany’s Exploration for Seafloor Massive Sulfides in the Indian Ocean - Ulrich Schwarz-Schampera; Ralf Freitag; Harold Gibson; Hendrik Mueller (International Marine Minerals Society, 2018)
INTRODUCTION Germany has a long history in marine research in the Indian Ocean. The first German scientific cruise started in 1964, followed by a series of state-sponsored research cruises between 1983 and 1995 leading to the first finding of polymetallic sulfides in the Indian Ocean. The research included regional bathymetric, geological, structural, volcanological, petrological and hydrothermal investigations along the Carlsberg Ridge and the Central Indian Ridge (CIR). Early environmental base line studies covered oceanographic and sedimentology aspects. In 2010, BGR took the initiative for the preparation of a license application for the exploration of polymetallic sulfides with the International Seabed Authority (ISA), and prospecting started in 2011 along the southern Central (CIR) and the northern Southeast Indian Ridge (SEIR) in the southwestern Indian Ocean (cruises INDEX 2011 on board R/V Sonne), INDEX 2012 (R/V Fugro Gauss), INDEX 2013/1-2 (R/V Sonne) and INDEX 2014 (R/V Pelagia). After three years of resource-oriented and environmental base line studies, BGR, in order for the Federal Ministry for Economic Affairs and Energy (BMWi), applied for an exploration license which was approved by and subsequently signed with the ISA in 2015. The license gave permission to start a detailed exclusive resource-oriented exploration program in the license area. The program includes the outline of potential ore deposits and a resource assessment but also extensive and detailed base line studies for the sustainable protection of the marine environment in the license area. The license contract has a fifteen years lifetime and may allow the application for a subsequent mining license. The exploration aims at the identification of inactive polymetallic sulfide deposits, formed below former discharge zones of hot hydrothermal fluids on the ocean floor (“black smoker” systems), by advanced and modern exploration techniques.